The Effectiveness Of Application Of Mind Mapping Learning Models On The Problems Of The Story Viewed From The Mathematic Communication Ability Of Vocational School Student - Novita, Tita (IKIP Siliwangi, 2020)
This article presents research on the effectiveness of learning using mind mapping learning models and experimental research methods with a pre-experimental design: one-shot case study design using purposive sampling, for vocational students of class XI in the academic year 2019/2020 on mathematical questions in the form of story questions. the purpose of this study is to describe the effectiveness of students' mathematical communication skills using mind mapping learning models, obtain a number of student problems in the process of communicating the form of mathematical problem problems with the form of story problems. Based on the analysis of the data obtained by the results of research at the destination school shows that the percentage of students who have good mathematical communication skills of students is less than 70%. Thus in the form of story questions, mind mapping learning models are not effective in terms of students' mathematical communication skills